Infrastructure and human capital development: an empirical analysis - Chinwendu Benedette Onugha; Abimbola Oluwaseun Oladipo (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
For years, Nigeria has ranked low in human capital development, largely due to inadequate infrastructure that needs improvement. In light of this, this study empirically examines the impact of infrastructure on human capital development in Nigeria using data sourced from the World Bank's Development Indicators. The data covers the period 1999 to 2022, and the analysis uses the vector error correction mechanism (VECM) method. Findings indicate that water access and tax revenue have positive but insignificant impacts on HDI, while internet access and population growth have significant positive impacts. Conversely, electricity access has a negative and insignificant impact on human capital development in Nigeria. Therefore, this study recommends that the government provide adequate infrastructure facilities for the well-being of its citizens.